The Diorama Effect: Gas, Politics, and Opera in the 1825 Paris Diorama - Bowen, Dore (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2014)
The diorama on the rue Sanson in Paris (1822–39) created a blended image by rotating the auditorium between two tableaux, each painted back and front and illuminated with colored light to create a sense of animation. What I call the “diorama effect” is the way the diorama used projection and reflection—both literally and figuratively—to create the illusion of places and characters known to the audience while simultaneously dissolving these references, seemingly into thin air. The 1825 diorama, the example in this essay, featured a tableau by Charles-Marie Bouton depicting a view of Paris and its new gas meter, and a second tableau by Louis Daguerre presenting a colonnade that disappears. To understand the way that these tableaux participated in then-contemporary debates on gaslight each is read in relation to narratives from the time—notably, the program notes for the diorama, the popular fairy tale of Aladdin and the magic lamp, and public debates in which the gas lamp figures as a political symbol of insurrection or, conversely, as a romantic symbol of exoticism.